ألفاظ العموم الذي أريد به الخصوص من خلال تراجم الصحيح لابن خزيمة في كتابي الوضوء والصوم: The phrases of generality that are intended to be specific in the chapter headings of the Sahih by Ibn Khuzaymah via the chapters of Ablution [Wudu’] and Fasting - Bint Zarrar, Aisha; Jibo , Salihu Musa (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث جاء هذا البحث بعنوان: "ألفاظ العموم الذي أُريد به الخصوص من خلال تراجم الصحيح لابن خزيمة، في كتابي الوضوء والصوم"، لدراسة أحد أنواع العموم في علم أصول الفقه، وتسليط الضوء على استخدام ابن خزيمة لهذا النوع في كتابه "الصحيح"، من خلال تراجمه في كتابي الوضوء والصوم. وتكمن مشكلة البحث في قلة الدراسات التي تناولت "صحيح ابن خزيمة" من الجانب الفقهي والأصولي، على الرغم من غناه العلمي، واقتصار أغلب الاهتمام على جانبه الحديثي، مع إغفال ما تحمله تراجمه من دلالات فقهية وأصولية. ويهدف البحث إلى بيان جهود ابن خزيمة العلمية، والتعريف بمفاهيم العموم والخصوص وأنواعهما، واستعراض أنواع التراجم في كتابه، ثم التطبيق على التراجم التي ورد فيها هذا النوع من العموم. وقد اقتضت طبيعة البحث اتباع المنهج الاستقرائي والتحليلي. وتبرز أهمية الدراسة في الكشف عن دقة ابن خزيمة الأصولية في تراجمه، وأثر معرفة ألفاظ العموم والخصوص في فهم النصوص واستنباط الأحكام، وقد توصلت الدراسة إلى أن ابن خزيمة استخدم ألفاظ العموم الذي أُريد به الخصوص – وإن لم يكن ذلك بكثرة – وأن أكثر تراجمه جاءت واضحة في دلالتها، مما يبرز أهمية العناية بهذا الجانب المهمل من كتابه. الخصوص، الحديث، تراجم الحديث، ابن خزيمة. ABSTRACT This research, titled " The phrases of generality that are intended to be specific in the chapter headings of the Sahih by Ibn Khuzaymah via the chapters of Ablution [Wudu’] and Fasting," aims to study a specific type of general expression in Usul al-Fiqh - namely, general terms intended for specific meaning - and to highlight how Ibn Khuzaymah used this type in his book Sahih, particularly in the chapters on purification and fasting. The problem addressed by this study lies in the lack of scholarly attention given to Sahih Ibn Khuzaymah from a jurisprudential and methodological perspective, despite its rich content. Most previous studies have focused primarily on its hadith content, overlooking the jurisprudential and Usuli implications found in its chapter headings. The study seeks to explore Ibn Khuzaymah’s scholarly contributions, define the concepts of generality and specificity and their types, analyze the types of chapter headings in his Sahih, and apply these to examples where general terms were used with specific intent. The research adopts an inductive and analytical methodology. Its significance lies in uncovering the Usuli precision in Ibn Khuzaymah’s chapter headings and demonstrating the impact of understanding general and specific expressions on interpreting texts and deriving rulings. The study concludes that although Ibn Khuzaymah did not frequently use general terms intended for specificity, when he did, the meanings of his chapter headings were generally clear - highlighting the importance of this overlooked aspect of his work.